2019
DOI: 10.4251/wjgo.v11.i4.281
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of tumor necrosis factor-α pathway survival genes and of the receptor TNFR2 in gastric cancer

Abstract: BACKGROUND Gastric carcinogenesis can be induced by chronic inflammation triggered by Helicobacter pylori ( H. pylori ) infection. Tumor necrosis factor (TNF)-α and its receptors (TNFR1 and TNFR2) regulate important cellular processes, such as apoptosis and cell survival, and the disruption of which can lead to cancer. This signaling pathway is also modulated by microRNAs (miRNAs), altering gene expression. AIM To ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…These genes, which have been reported to participate in the occurrence, development, and metastasis of tumors, were also the core genes in osteoblasts whose expression changed significantly under stimulation with F. nucleatum , as shown by RNA-seq analysis. NFKB2 has been observed to be upregulated in gastric cancer tissues ( Rossi et al, 2019 ), and its altered expression can collaborate with heterozygous Kras MUT to drive tumorigenesis but decreases the metastatic potential of pancreatic ductal adenocarcinoma ( Mueller et al, 2018 ). The upregulation of Tnfrsf1b, which belongs to the TNF receptor superfamily, has also been found in gastric cancer tissues ( Rossi et al, 2019 ), and Tnfrsf1b can promote colorectal carcinogenesis ( Liu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These genes, which have been reported to participate in the occurrence, development, and metastasis of tumors, were also the core genes in osteoblasts whose expression changed significantly under stimulation with F. nucleatum , as shown by RNA-seq analysis. NFKB2 has been observed to be upregulated in gastric cancer tissues ( Rossi et al, 2019 ), and its altered expression can collaborate with heterozygous Kras MUT to drive tumorigenesis but decreases the metastatic potential of pancreatic ductal adenocarcinoma ( Mueller et al, 2018 ). The upregulation of Tnfrsf1b, which belongs to the TNF receptor superfamily, has also been found in gastric cancer tissues ( Rossi et al, 2019 ), and Tnfrsf1b can promote colorectal carcinogenesis ( Liu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…NFKB2 has been observed to be upregulated in gastric cancer tissues ( Rossi et al, 2019 ), and its altered expression can collaborate with heterozygous Kras MUT to drive tumorigenesis but decreases the metastatic potential of pancreatic ductal adenocarcinoma ( Mueller et al, 2018 ). The upregulation of Tnfrsf1b, which belongs to the TNF receptor superfamily, has also been found in gastric cancer tissues ( Rossi et al, 2019 ), and Tnfrsf1b can promote colorectal carcinogenesis ( Liu et al, 2018 ). Fbln5 can inhibit epithelial cell proliferation and carries out tumor-promoting and tumor-protective functions in breast lesions ( Karanis et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, related studies indicated that miR-130a-3p was upregulated in GC and promoted the invasion of GC cells [63]. Rossi et al [64] indicated that the miR-130a in diffuse GC was higher than that in intestinal type GC. In addition, some studies suggested that miR-130a was downregulated in GC and was related to the migration and metastasis of GC [65].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies [ 51 , 52 , 53 ] have shown that miR-19a is involved in the proliferation of human gastric cancer (GC). Yuan et al [ 51 ] demonstrated that miR-17-92a-1 Cluster Host Gene (MIR17HG)-derived miR-18a and miR-19a-3p coordinately mediate GC cell metastasis by directly inhibiting mothers against decapentaplegic homolog 2 (SMAD2) expression and upregulating Wingless-related integration site (Wnt)/β-catenin signaling.…”
Section: Roles and Mechanisms Of Action Of Mir-19a In Clinical Cancer Featuresmentioning
confidence: 99%